Effect of anaemia and iron deficiency in heart failure with mildly reduced ejection fraction - Schupp, Tobias; Weidner, Kathrin; Reinhardt, Marielen; Abel, Noah; Schmitt, Alexander; Lau, Felix; Kittel, Maximilian; Bertsch, Thomas; Weiß, Christel; Behnes, Michael; Akın, Ibrahim (European journal of clinical investigation, 2024)
Objective The present study aims to clarify the prevalence and prognostic impact of anaemia and iron deficiency in patients with heart failure with mildly reduced ejection fraction (HFmrEF). Background The prognostic impact of anaemia and iron deficiency in HFmrEF has not yet been clarified. Methods Consecutive patients with HFmrEF were retrospectively included at one institution from 2016 to 2022. Patients with anaemia (i.e. haemoglobin <13 g/dL in males and < 12 g/dL in females) were compared to patients without, respectively patients with or without iron deficiency. The primary endpoint was all-cause mortality at 30 months (median follow-up), secondary endpoints comprised HF-related rehospitalisation. Results Two thousand one hundred and fifty four patients with HFmrEF with a median haemoglobin level of 12.2 g/dL were included. Anaemia was present in 52% of patients with HFmrEF and associated with a higher risk of all-cause mortality (44% vs. 18%; HR = 3.021; 95% CI 2.552-3.576; p =.001) and HF-related rehospitalisation (18% vs. 8%; HR = 2.351; 95% CI 1.819-3.040; p =.001) at 30 months, which was confirmed after multivariable adjustment. Although iron status was infrequently assessed in anaemics with HFmrEF (27%), the presence of iron deficiency was associated with higher risk of rehospitalisation for worsening HF (25% vs. 15%; HR = 1.746; 95% CI 1.024-2.976; p =.038), but not all-cause mortality (p =.279) at 30 months. Conclusion Anaemia and iron deficiency are very common in atleast half of patients with HFmrEF and independently associated with adverse long-term prognosis.